Analysis of Students' Learning Motivation Using Flipbook Media in Elementary School - Isti Windi Astuti; Ana Andriani (UM Purwokerto Press, 2025)
Learning motivation is an important factor in the success of students in achieving learning objectives. This study aims to determine the effectiveness of using flipbook media in an effort to enhance students' learning motivation. Flipbook, as an interactive learning medium, is expected to increase students' interest and make the learning process more enjoyable. The research method used is qualitative, employing a descriptive qualitative research design. The results of the study indicate that the use of flipbook media can enhance students' learning motivation compared to conventional teaching methods. By using flipbook media, students are more motivated to learn because it creates an engaging and interactive learning experience.